(untitled) (CIPEEX, 2024)
WHILE ADVANCES IN ANTIRETROVIRAL TREATMENT HAVE REVOLUTIONIZED THE PROGNOSIS OF HUMAN IMMUNODEFICIENCY (HIV)-INFECTED PATIENTS, CARDIOVASCULAR COMPLICATIONS REMAIN THE LEADING CAUSE OF DEATH IN THESE PATIENTS MAINLY DUE TO AN INCREASED CARDIOVASCULAR RISK COMPARED TO THE GENERAL POPULATION. THEREFORE, HIV-INFECTED INDIVIDUALS HAVE A RESIDUAL CARDIOVASCULAR RISK FOR CARDIOVASCULAR EVENTS THAT MAY JUSTIFY ADDITIONAL PREVENTIVE TREATMENT. THE MAIN OBJECTIVE OF THIS WORK IS TO EVALUATE THE SAFETY OF USING STATINS FOR PRIMARY PREVENTION OF CARDIOVASCULAR DISEASES IN PEOPLE WITH HIV. THIS IS A DESCRIPTIVE STUDY OF INTEGRATIVE LITERATURE REVIEW, CONDUCTED WITH SEARCHES IN THE DATABASES PUBMED, BVS, SCIELO AND GOOGLE SCHOLAR. MESH TERMS WERE ESTABLISHED FOR THE SEARCH FOR STUDIES THAT ADDRESSED THE THEME: "HIV INFECTIONS", "HEART DISEASE RISK FACTORS" AND "STATINS". GIVEN THESE PERSPECTIVES, STUDY RESULTS HAVE SHOWN THAT FOR PEOPLE ‰¥40 YEARS OF AGE WITH HIV AND A LOW-DENSITY LIPOPROTEIN CHOLESTEROL ‰¥190 AND/OR A 10-YEAR ASCVD SCORE ‰¥7.5 PERCENT, IT IS RECOMMENDED THE USE OF A STATIN. FURTHERMORE, STATIN IS ALSO SUGGESTED FOR THOSE PATIENTS WITH A 10-YEAR ASCVD SCORE OF 5 TO 7.4 PERCENT. FOR THOSE AT LOWER RISK, THE USE OF STATINS IS ALSO EVALUATED, BUT THE ABSOLUTE BENEFIT IS LOWER.